The Relationship Between Mental Wellbeing and Post Traumatic Stress Disorder (PTSD) Among Trauma Survivors: Spiritual Jihad as a Mediatior - Rameen Rehman; Sania Arshad; Eman Sarwar; Aneela Mushtaq; Amina Perveen (Penerbit Hellow Pustaka, 2026)
The aim of this study to explore the relationship between mental wellbeing and post traumatic stress disorder (PTSD) among trauma survivors: spiritual jihad as a mediator. Trauma exposure is frequently associated with post-traumatic stress disorder (PTSD), which can reduce mental wellbeing. However limited literature has examined the adverse psychological outcomes of trauma & culturally grounded protective factors that may influence this relationship. Using a cross-sectional research design, data were collected from 100 trauma survivors (50 males and 50 females) aged 18 to 30 years who had been clinically diagnosed with PTSD. Participants were recruited from multiple hospitals using purposive sampling. Mental wellbeing was assessed using the Warwick–Edinburgh Mental Wellbeing Scale, PTSD severity was measured with the National Stressful Events Survey PTSD Short Scale, and spiritual jihad was measured using the Spiritual Jihad Mindset Measure. Data were analyzed using linear regression and mediation analysis via PROCESS in SPSS-25. Results showed that spiritual jihad is negatively related to mental wellbeing and positively related to PTSD, and it significantly mediated the relationship between the two variables. In conclusion, spiritually informed approaches may support resilience among trauma survivors.